2020
DOI: 10.1063/5.0014944
|View full text |Cite
|
Sign up to set email alerts
|

Ion accumulation by a dust cloud in a dc discharge

Abstract: The ion accumulation within the negatively charged dust cloud embedded in a plasma of dc glow discharge has been studied numerically under the conditions corresponding to recent experiments. The characteristics of neon plasma in a positive column of dc discharge with various densities of micron-sized particles have been simulated by a diffusion-drift model with the use of experimental values of parameters of dust clouds. The model considers an additional gas heating associated with the presence of a dust compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…A certain group of methods requires assumptions on the spatial distribution of plasma parameters [15,16] and/or rely on the exact values of plasma parameters [19]. Values of the plasma parameters are often taken from measurements in dust-free plasmas, whereas it has been shown that dust strongly affects the local values of plasma parameters as well as their global distributions [9,[20][21][22][23]. All the above-mentioned issues limit the accuracy of the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…A certain group of methods requires assumptions on the spatial distribution of plasma parameters [15,16] and/or rely on the exact values of plasma parameters [19]. Values of the plasma parameters are often taken from measurements in dust-free plasmas, whereas it has been shown that dust strongly affects the local values of plasma parameters as well as their global distributions [9,[20][21][22][23]. All the above-mentioned issues limit the accuracy of the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The relative overheating coefficient η Q is useful, first of all, for technologies and processes at low and cryogenic temperatures, when heating is undesirable [24][25][26][27][28]. As was demonstrated in [18], at low discharge currents (I < 1 mA) a gain in the relative heating is quite large (η Q > 10), but it disappears with increasing the discharge current. For instance, for a discharge in neon containing microparticles of several microns in diameter within the pressure range of 40 to 120 Pa, the relative overheating coefficient is less than one (η Q < 1) at the current I > 2 mA.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, such conditions are realized in a nonequilibrium low-temperature plasma of self-sustaining low-pressure electric discharges [21][22][23]. From the viewpoint of heat release, gas-discharge plasma with charged microparticles represents a more efficient system, which produces and concentrates ions [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations